Formic Acid‐Assisted Selective Hydrogenolysis of 5‐Hydroxymethylfurfural to 2, 5‐Dimethylfuran over Bifunctional Pd Nanoparticles Supported on N‐Doped Mesoporous Carbon. Issue 12 (22nd January 2021) - Hu, Bin; Warczinski, Lisa; Li, Xiaoyu; Lu, Mohong; Bitzer, Johannes; Heidelmann, Markus; Eckhard, Till; Fu, Qi; Schulwitz, Jonas; Merko, Mariia; Li, Mingshi; Kleist, Wolfgang; et al.
Abstract: Biomass‐derived 5‐hydroxymethylfurfural (HMF) is regarded as one of the most promising platform chemicals to produce 2, 5‐dimethylfuran (DMF) as a potential liquid transportation fuel. Pd nanoparticles supported on N‐containing and N‐free mesoporous carbon materials were prepared, characterized, and applied in the hydrogenolysis of HMF to DMF under mild reaction conditions. Quantitative conversion of HMF to DMF was achieved in the presence of formic acid (FA) and H2 over Pd/NMC within 2 h. The reaction mechanism, especially the multiple roles of FA, was explored through a detailed comparative study by varying hydrogen source, additive, and substrate as well as by applying in situ ATR‐IR spectroscopy. The major role of FA is to shift the dominant reaction pathway from the hydrogenation of the aldehyde group to the hydrogenolysis of the hydroxymethyl group via the protonation by FA at the C‐OH group, lowering the activation barrier of the C−O bond cleavage and thus significantly enhancing the reaction rate. XPS results and DFT calculations revealed that Pd 2+ species interacting with pyridine‐like N atoms significantly enhance the selective hydrogenolysis of the C−OH bond in the presence of FA due to their high ability for the activation of FA and the stabilization of H − . Abstract : Quantitative conversion of HMF to DMF was achieved in the presence of formic acid and H2 over the bifunctional Pd/NMC catalyst within 2 h. Experimental investigation and DFT calculation revealed that formic acid significantly enhances the reaction rate and shifts the dominant reaction pathway from the hydrogenation of the aldehyde group to the hydrogenolysis of the hydroxymethyl group via its protonation.